Stool metabolome-microbiota evaluation among children and adolescents with obesity, overweight, and normal-weight using 1H NMR and 16S rRNA gene profiling - Jaimes, José Diógenes; Slavíčková, Andrea; Hurych, Jakub; Cinek, Ondřej; Nichols, Ben; Vodolánová, Lucie; Černý, Karel; Havlík, Jaroslav (PloS one, 2021)
Characterization of metabolites and microbiota composition from human stool provides powerful insight into the molecular phenotypic difference between subjects with normal weight and those with overweight/obesity. The aim of this study was to identify potential metabolic and bacterial signatures from stool that distinguish the overweight/obesity state in children/adolescents. Using 1H NMR spectral analysis and 16S rRNA gene profiling, the fecal metabolic profile and bacterial composition from 52 children aged 7 to 16 was evaluated. The children were classified into three groups (16 with normal-weight, 17 with overweight, 19 with obesity). The metabolomic analysis identified four metabolites that were significantly different (p < 0.05) among the study groups based on one-way ANOVA testing: arabinose, butyrate, galactose, and trimethylamine. Significantly different (p < 0.01) genus-level taxa based on edgeR differential abundance tests were genus Escherichia and Tyzzerella subgroup 3. No significant difference in alpha-diversity was detected among the three study groups, and no significant correlations were found between the significant taxa and metabolites. The findings support the hypothesis of increased energy harvest in obesity by human gut bacteria through the growing observation of increased fecal butyrate in children with overweight/obesity, as well as an increase of certain monosaccharides in the stool. Also supported is the increase of trimethylamine as an indicator of an unhealthy state.
Keywords: obezita; Gastrointestinal Microbiome; feces; Humans; Metabolome; dítě; Metabolomics; Child; Pediatric Obesity; Female; RNA ribozomální 16S; metabolomika; lidé; RNA, Ribosomal, 16S; Feces; metabolom; ženské pohlaví; obezita dětí a dospívajících; protonová magnetická rezonanční spektroskopie; Male; Adolescent; Czech Republic; Obesity; střevní mikroflóra; Bacteria; Česká republika; mužské pohlaví; Proton Magnetic Resonance Spectroscopy; mladiství